Pelatihan WhatsApp Business: Meningkatkan Efisiensi dan Kinerja Bank Sampah Sakura Palembang - M Arief Rahman; Rika Sadariawati; Alem Pameli; Fitrianto Puja Kesuma (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
WhatsApp Business training has been conducted to improve the quality of management of Sakura Waste Bank Palembang. This activity aims to train managers and employees in operating and using the WhatsApp Business application in daily activities. The results of the training showed that participants were satisfied and able to apply the knowledge gained. It is hoped that this training can positively contribute to improving the efficiency and performance of Sakura Waste Bank